ANALISIS STRATEGI PENGELOLAAN PASAR TRADISIONAL SEKETENG SUMBAWA BESAR DALAM MENINGKATKAN KEPUASAN PELANGGAN - Riani, Farida; Syafruddin, S (Jurnal Ekonomi & Bisnis, 2024)
This study aims to analyze the strategy of Seketeng traditional market management in Sumbawa Besar to increasing customer satisfaction. The type of this study was descriptive study with qualitative approach. The type of data used was qualitative data obtained from primary sources using research instruments in the form of interview guidelines. The informants in this study consisted of bureaucrats from government agencies/ institutions/ agencies in Sumbawa District, academics, traders, and customers at the Seketeng traditional market, Sumbawa Besar. The data analysis technique used was analysis hierarchy process (AHP), which measures the consistency level of the strategy of Seketeng traditional market management in Sumbawa Besar to increasing customer satisfaction. The results of this study showed that the revitalization of market facilities and infrastructure had the highest level of importance compared to other alternative criteria, so that it becomes a priority strategy for managing the Seketeng traditional market ini Sumbawa Besar to increasing consumer satisfaction. Therefore, the market revitalization program must be carried out optimally to improve the physical conditions and spatial layout of the Seketeng traditional market in Sumbawa Besar so as to increase consumer satisfaction. That was followed by other alternative criteria in sequence according to their level of importance, namely strengthening market management, establishing regional rules or regulations, market expansion, and strengthening trader capital.